Behavioral effects of interacting imipramine and other drugs with d-Amphetamine, cocaine, and tetrabenazine - Scheckel, Carl (1964)
A variety of drugs including Anticholinergics, antihistamines, MAO inhibitors, miscellaneous stimulants and depressants (“tranquilizers”), and imipramine-like compounds were tested in rats conditioned to respond in the Sidman, continuous avoidance procedure. Several doses of each drug were tested to determine the minimum effective dose that increased (stimulated) or decreased (depressed) the rate of lever pressing. Behaviorally inactive doses of each drug were then tested in three drug interaction experiments: 1) amphetamine potentiation, 2) cocaine potentiation, 3) stimulation with a nondepressant dose of tetrabenazine. Pretreatment with imipramine-like compounds or cocaine produced stimulation in all three drug interaction experiments. Promethazine, tyramine, guanethidine, as well as a few anticholinergics, and MAO inhibitors potentiated amphetamine and cocaine, but did not stimulate with tetrabenazine. Chlorpromazine, azacyclonol, methylphenidate, phenindamine, and promazine were inactive in the three drug interaction tests. Imipramine-like drugs differed qualitatively from all other agents tested in that they had no systematic effects when given alone, but consistently produced stimulation when combined with a small, nondepressant dose of tetrabenazine. A comparison of the present behavioral data with previous biochemical findings indicates that imipramine induces a stimulant (or antidepressant) effect by increasing the reactivity of central mechanisms to the action of “free” norepinephrine